Chronic encapsulated intracerebral haematoma: pathogenetic and diagnostic considerations. Issue 11 (November 1989) - Fiumara, E; Gambacorta, M; D'Angelo, V; Ferrara, M; Corona, C
Abstract : Two cases of chronic encapsulated intracerebral haematoma are reported. The patients presented with progressive neurological deficits. Computed tomography scan showed a roundish, intracerebral lesion, that revealed ring blush after contrast infusion, with mass effect. At operation a thick, fibrous, brownish capsule, containing clots in different states of formation, was removed. The hypothesis of capsule formation due to an exuberant proliferation of arachnoidal fibroblasts, is discussed. Differentiation between encapsulated intracerebral haematoma and other chronic intracerebral blood collections is considered mandatory for appropriate treatment.